Surgical Treatment Options for Giant Cell Tumors of Bone Around the Knee Joint: Extended Curettage or Segmental Resection? - He, Hongbo; Zeng, Hao; Luo, Wei; Liu, Yupeng; Zhang, Can; Liu, Qing (Frontiers in Oncology, 2019)
Aims: This study aimed to compare and evaluate the oncological and functional prognosis of two surgical approaches for giant cell tumor of the bone (GCTB) around the knee joint and provide worthy suggestion for clinical treatment. Patients and Methods: This study included 93 patients, who were divided into the extended curettage (EC) group and segmental resection (SR) group. Relevant preoperative and postoperative data were collected, oncological and functional prognosis were evaluated, and postoperative complications of the two groups were analysed. Local recurrence was assessed via clinical and radiological tests. Functional prognosis was evaluated using the Musculoskeletal tumor Society (MSTS) scoring system. Results: The EC group had 69 patients; it included 57 primary cases and 12 recurrent cases. The SR group had 24 patients (12 men and 12 women; mean age, 34.9 years), including 15 primary cases and 9 recurrent cases. In this study, six cases (6.5%; EC group, 5 cases; SR group 1 case) recurred within 18 months postoperatively. There was a significant difference in the mean MSTS score between the two groups (p<0.001). Nononcologic complications occurred frequently in the EC group than in the SR group (28.0% versus 16.7%), but no complications had serious consequences, and the functional prognosis was not affected. Conclusion: EC and SR for GCTB around the knee joint can achieve satisfactory oncological prognosis, but we should individually select the most suitable surgical method according to Campanacci grade, age, and long-term complications of patients and consider the functional prognosis to ensure excellent oncological prognosis.